Accurate displacement detection with a computer-aided interferometric measuring system - (:unkn) unknown (Polish Academy of Sciences, 2012)
In this study, real time measurement of the linear expansion of industrial material undergoing temperature change by using a computer-aided interferometric measuring technique with micrometer accuracy is attempted. Aluminum and copper were subjected to temperature change in the thermal expansion experiment unit (LETI-1) causing them to expand linearly. The fringe number in the interference symbol, which includes the information about linear expansion and temperature change were transferred to a computer via a data acquisition card, graphed by a program created in the LabVIEW environment, and the amount of linear expansion was detected in real time.